2009
DOI: 10.1007/s10278-009-9177-9
|View full text |Cite
|
Sign up to set email alerts
|

Why Does It Take Longer to Read Digital Than Film-Screen Screening Mammograms? A Partial Explanation

Abstract: Digital screening mammograms (DM) take longer to interpret than film-screen screening mammograms (FSM). We evaluated what part of the process takes long in our reading environment. We selected cases from those for which timed readings had been performed as part of a previous study. Readers were timed as they performed various computer manipulations on groups of DM cases and as they moved the alternator and adjusted lighting and manual shutters for FSM cases. Subtracting manipulation time from the original inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Two studies from radiology support these impressions. The first, an observational time motion study,[ 11 ] found that soft copy interpretation takes longer to read primarily due to longer computer manipulation times (bringing up the images, enlarging them to 100% resolution, and panning through the image) and increased time gazing at the image. The second study[ 12 ] found that the overall productivity of the radiologists increased 10-30% after the conversion, likely due to more rapid access to old images and reports, elimination of interruptions by personnel looking for films, better ability to distribute the workload across all radiologists, and constant displays of unread examinations making remaining workload more observable.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies from radiology support these impressions. The first, an observational time motion study,[ 11 ] found that soft copy interpretation takes longer to read primarily due to longer computer manipulation times (bringing up the images, enlarging them to 100% resolution, and panning through the image) and increased time gazing at the image. The second study[ 12 ] found that the overall productivity of the radiologists increased 10-30% after the conversion, likely due to more rapid access to old images and reports, elimination of interruptions by personnel looking for films, better ability to distribute the workload across all radiologists, and constant displays of unread examinations making remaining workload more observable.…”
Section: Resultsmentioning
confidence: 99%
“…Absence of a significant time difference between reading the sets with and without the zoom functions enabled is an important finding in this study. Previous studies have noted slow reporting times due to a large amount of possible manipulations, including electronic magnification. However, those authors recorded separately the manipulation time and the decision‐making time, which was different from our study, when the overall time was recorded from the moment a reader began the test until he or she completed it.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that better reader performance will occur when magnification is used in the case of images that are not displayed at full resolution, although evidence of the benefit of magnification in routine mammographic interpretation is not obvious . Conversely, manipulation of images by electronic magnification (‘zooming’) may increase reporting times and distort the readers' perception of lesions . Although performing the electronically magnified search for calcifications on digital images is more time‐consuming than holding a magnifier to review screen‐film images, readers might fail to detect some lesions if they omit the zooming tool.…”
Section: Introductionmentioning
confidence: 99%
“…The higher cost of FFDM is linked to the cost of purchasing and maintaining the digital machines as well as the increased time it takes to interpret FFDM 9 due to computer manipulation time. 10 …”
Section: Introductionmentioning
confidence: 99%